2016
DOI: 10.1074/jbc.m115.684373
|View full text |Cite
|
Sign up to set email alerts
|

Differential α4(+)/(−)β2 Agonist-binding Site Contributions to α4β2 Nicotinic Acetylcholine Receptor Function within and between Isoforms

Abstract: Two ␣4␤2 nicotinic acetylcholine receptor (␣4␤2-nAChR) isoforms exist with (␣4) 2 (␤2) 3 and (␣4) 3 (␤2) 2 subunit stoichiometries and high versus low agonist sensitivities (HS and LS), respectively. Both isoforms contain a pair of ␣4(؉)/(؊)␤2 agonist-binding sites. The LS isoform also contains a unique ␣4(؉)/ (؊)␣4 site with lower agonist affinity than the ␣4(؉)/(؊)␤2 sites. However, the relative roles of the conserved ␣4(؉)/(؊)␤2 agonist-binding sites in and between the isoforms have not been studied. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(60 citation statements)
references
References 52 publications
4
55
1
Order By: Relevance
“…There was, however, one exception: at the highest lynx1 mRNA coinjection only, function per cell‐surface (α3β4) 2 β4nAChR increased significantly. Of interest, function per receptor levels in the absence of lynx1 are <5 μA/fmol across all α3β4*‐nAChR isoforms, which is much lower than that previously measured for α4β2*‐nAChR using a similar approach (48, 74). Given the greater bursting behavior and slower macroscopic desensitization of α3β4*‐ (references cited above, data from this study) vs .…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…There was, however, one exception: at the highest lynx1 mRNA coinjection only, function per cell‐surface (α3β4) 2 β4nAChR increased significantly. Of interest, function per receptor levels in the absence of lynx1 are <5 μA/fmol across all α3β4*‐nAChR isoforms, which is much lower than that previously measured for α4β2*‐nAChR using a similar approach (48, 74). Given the greater bursting behavior and slower macroscopic desensitization of α3β4*‐ (references cited above, data from this study) vs .…”
Section: Discussioncontrasting
confidence: 55%
“…This explanation also fits with a previous observation that β4‐nAChR subunits lack endoplasmic reticulum–retention/retrieval motifs that were found within β2‐nAChR subunits, and have an endoplasmic reticulum–export motif missing from β2 subunits (75), which results in increased surface expression—potentially at the expense of quality control. This explanation is further reinforced by the fact that surface expression of α3β4*‐nAChR—especially of the isoform that contains 3 β4 subunits—is much higher than that of α4β2*‐nAChR as measured in our previous studies (48, 74), and, as demonstrated in the current study, removal of these putative quiescent (α3β4) 2 β4‐nAChRs from the cell surface can be reversed by GPI anchor cleavage, which suggests a possible cell‐surface role for lynx1 in this quality control phenomenon.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In both the brain and the periphery nicotine acts on nicotinic acetylcholine receptors (nAChR), cation channels made up of a combination α-and β-type subunits arranged as a pentamer around a central pore (Albuquerque, Pereira, Alkondon, & Rogers, 2009;Morales-Perez, Noviello, & Hibbs, 2016). The identity of the individual subunits and the stoichiometry of α and β subunits within an assembled nAChR determine many channel properties, including sensitivity to both endogenous and exogenous ligands, kinetics of ligand binding, the amplitude and identity of ionic currents that flow through the channel, and channel open time (George et al, 2017;Lucero et al, 2015;Mazzaferro, Bermudez, & Sine, 2016;Stokes & Papke, 2012). In addition, each nicotinic subunit is expressed in distinct, though overlapping, patterns in many cell types throughout the brain (Sargent, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The α4β2 nAChR comprises two α4β2 pairs and a fifth subunit that can be β2 or α4, and this subunit difference produces two alternate receptor isoforms, the (α4β2) 2 β2 and (α4β2) 2 α4 nAChRs (Nelson et al , ; Moroni et al , ) (Figure A). The alternative receptors display strikingly different sensitivities to activation by ACh and other agonists (Nelson et al , ; Moroni et al , ; Harpsøe et al , ; Mazzaferro et al , ; Timmermann et al , ; Absalom et al , ; Lucero et al , ), high‐affinity desensitization (Marks et al , ; Benallegue et al , ), sensitivity to allosteric modulators (Moroni et al , ; Olsen et al , ; Alcaino et al , ; Jin et al , ) and single‐channel properties (Mazzaferro et al , ). These differences are accounted for partly by an additional operational agonist site in the (α4β2) 2 α4 stoichiometry housed by the interface between the fifth subunit (an α4) and an adjacent α4 subunit (Harpsøe et al , ; Mazzaferro et al , ).…”
Section: Introductionmentioning
confidence: 99%